Understanding Using Of Audit Software By Auditor With Unified Theory Of Acceptance And Use Of Technology Construct - Lestara Permana, Gusi Putu; Anggi Puspitadewi, Made Ayu (Kompartemen : Jurnal Ilmiah Akuntansi, 2023)
The purpose of this research is to find out about how the acceptance of audit software by auditor. This research used Public Accountant Firm in Bali as the location there are 17 Firm. The sample in this study was 95 respondents based on purposive sampling technique with the calculation of the Lemeshow formula. The type of data in this study is quantitative data uses primary data sources that collected using a questionnaire. The analytical technique used is Structural Equation Modeling using Partial Least Square (SEM PLS). The results show that the auditors at the Public Accountant Firm in Bali can accept the use of audit software well which is based on the UTAUT model. UTAUT, namely performance expectancy, expectation of a more optimal performance by utilizing technology. Although aspects of social influence and voluntariness of use are not able to influence the acceptance of audit software for auditors at the Public Accountant Firm in Bali.